Die noodsaak van kulturele interaksie in Apologetiek: Handelinge 17:16-32 as motivering - Erasmus, Johan; Stoker, Henk (In die Skriflig/In Luce Verbi, 2017)
The need of cultural interaction in Apologetics: Acts 17:16–32 as explanatory statement. Acceptance of a secular-versus-holy dualism holds Christianity in a cultural prison and has the effect that the Christian faith becomes a compartmentalised entity, which oddly fits in a secular context, because it does not have an impact outside the church building. To be culturally effective in its communication, apologetics should make use of images and expressions that is known by the people it aims to reach. Interacting with their worldviews in a narrative form is also much more subtle than the use of an argumentative style of reasoning that emphasise differences. Arts have a particular ability to shape and analyse culture. Films can help Christian apologists to understand culture as well as to be in a better position to engage meaningfully with the world. In a similar way to which Paul made use of pagan insights and narratives in Acts 17, the themes of contemporary movies can be used by apologists. Paul’s strategy was not the syncretistic reconciliation of two incompatible worldviews, but subversion through giving Greek ideas new meaning by placing them in a monotheistic context. When apologetics makes use of stories saturated with Christian themes, it can address secular imagination with an understanding of God and the world which they would not otherwise have considered.
free